2014
DOI: 10.1007/s00330-014-3348-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of malposition of the branch pulmonary arteries using cardiovascular computed tomography angiography

Abstract: MBPA has a hospital-based prevalence of 0.33% among congenital heart disease patients. Classic type of MBPA was more common than lesser type. All MBPA patients had associated cardiovascular anomalies, 33% had secondary airway compression. CCTA delineates the anatomy of MBPA, associated cardiovascular and airway abnormalities. CCTA is beneficial in MBPA for preoperative evaluation and planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 19 publications
4
11
0
1
Order By: Relevance
“…El "crisscross" de arterias pulmonares constituye muchas veces un hallazgo en el estudio de otras malformaciones cardíacas, en exámenes ecocardiográficos o de otras técnicas imagenológicas como el Angio TAC de tórax, la resonancia cardíaca o el cateterismo 5 . Es una condición poco frecuente, con publicaciones de casos aislados y pequeñas series, pero la cifra global pudiera estar subestimada por falta de reporte o subdiagnóstico considerando que en la de los casos se presenta como una condición benigna.…”
Section: Discussionunclassified
“…El "crisscross" de arterias pulmonares constituye muchas veces un hallazgo en el estudio de otras malformaciones cardíacas, en exámenes ecocardiográficos o de otras técnicas imagenológicas como el Angio TAC de tórax, la resonancia cardíaca o el cateterismo 5 . Es una condición poco frecuente, con publicaciones de casos aislados y pequeñas series, pero la cifra global pudiera estar subestimada por falta de reporte o subdiagnóstico considerando que en la de los casos se presenta como una condición benigna.…”
Section: Discussionunclassified
“…If it occurs, it is related to associated cardiovascular anomalies like pulmonary arterial sling. 5,6,11,12 Crossed pulmonary arteries must be distinguished from pulmonary artery sling and anomalous origin of one pulmonary artery 3,5,10 and also from the abnormal course of the left pulmonary artery in the setting of a horseshoe lung. 8 Echocardiography is the primary method used to demonstrate crossed pulmonary arteries in most of the reported cases, as it was a safe and convenient economical image technique.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The exact prevalence of malposition of the branch pulmonary arteries is not known; Hui Liu, in his hospital-based study, found approximately 0.06% in the population who underwent chest CT or CT angiography. 6 Jue KL et al 1 suggested that this condition could result from a faulty differential growth within the pulmonary trunk during the partitioning of truncus arteriosus with a counterclockwise rotation of normally formed main and branch pulmonary arteries. 1,7 It is postulated that this malposition occurs at approximately 41 st day of development when the right and left pulmonary arteries ostia migrate towards each other.…”
mentioning
confidence: 99%
“…In the previously studies, crossed pulmonary arteries was often accompanied by congenital cardiovascular disease such as ventricular septal defect, right aortic arch, interrupted aortic arch and persistent truncus arteriosus, and chromosomal abnormalities such as 18 trisomy syndrome [1, 2, 5]. To our knowledge, crossed pulmonary arteries associated with single atrium as the only additional cardiac anomaly has not been reported so far.…”
Section: Case Presentationmentioning
confidence: 96%
“…Since the first description of crossed pulmonary arteries was provided by Jue et al in 1966, no more than 69 cases of crossed pulmonary arteries were diagnosed by echocardiography or three-dimensional computed tomographic imaging [1]. The prevalence of crossed pulmonary arteries is approximately 0.06 % in population who undergo chest CT or CTA [5]. The etiology of this anomaly is uncertain.…”
Section: Case Presentationmentioning
confidence: 99%